2018
DOI: 10.1016/j.jpainsymman.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Neonatal End-of-Life Comfort Care Guidelines Across America

Abstract: Context. Infants of age less than one year have the highest mortality rate in pediatrics. The American Academy of Pediatrics published guidelines for palliative care in 2013; however, significant variation persists among local protocols addressing neonatal comfort care at the end-of-life (EOL). Objectives. The purpose of this study was to evaluate current neonatal EOL comfort care practices and clinician satisfaction across America. Methods. After institutional review board approval (516005), an anonymous, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…That said, when providing interdisciplinary PPC services for children, it can be expected that most children do not have a malignancy [ 17 ] and about half of the patients would be infants. Despite the great need in neonatology, more than 45% of institution in Canada and the United States not have neonatal comfort care guidelines, and of those reporting institutional neonatal comfort care guidelines, 19.1% do not address pain symptom management [ 18 ]. More than 90% of respondents in the same study felt that their institution would benefit from further education and training in neonatal EOL care.…”
Section: Common Myths and Misconceptions In Pediatric Palliative Cmentioning
confidence: 99%
“…That said, when providing interdisciplinary PPC services for children, it can be expected that most children do not have a malignancy [ 17 ] and about half of the patients would be infants. Despite the great need in neonatology, more than 45% of institution in Canada and the United States not have neonatal comfort care guidelines, and of those reporting institutional neonatal comfort care guidelines, 19.1% do not address pain symptom management [ 18 ]. More than 90% of respondents in the same study felt that their institution would benefit from further education and training in neonatal EOL care.…”
Section: Common Myths and Misconceptions In Pediatric Palliative Cmentioning
confidence: 99%
“…Lack of education and training has frequently been cited as a barrier to the provision of consistent and comprehensive palliative and bereavement support in the neonatal setting ( 7 , 54 57 ). Haug et al ( 55 ) demonstrated, in a nationwide study, that fewer than a third of institutions offer any formal training for physicians or staff on perinatal palliative or comfort care. However, research has shown that professionals exhibit better emotional coping when they have been provided with education related to bereavement and end-of-life issues ( 56 , 58 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that professionals exhibit better emotional coping when they have been provided with education related to bereavement and end-of-life issues ( 56 , 58 60 ). For example, a strong majority (91.8%) of neonatologists involved in that study indicated that increased education in perinatal palliative and end-of-life care would be beneficial ( 55 ). Elements of self-care activity, as well as the symptoms and risk factors for both burnout and compassion fatigue, should be included in the education for perinatal palliative care professionals ( 7 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal end-of-life (EOL) care includes addressing pain and other distressing symptoms (1,7,10,11). Neonatal intensive care units (NICUs) are generally competent in EOL care of neonates; however, evidence shows there are wide variations in methods for evaluating and addressing symptoms (1,12). This variation likely stems from limited evidence regarding neonatal EOL symptom management given the lack of on-label neonatal pharmacologic treatments (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…This variation likely stems from limited evidence regarding neonatal EOL symptom management given the lack of on-label neonatal pharmacologic treatments (5,10). A 2016 survey showed only 55% of NICUs in the United States have a neonatal EOL guideline, and 45% do not have access to a palliative care team, showing there is much room for improvement regarding neonatal EOL care (1). This review aims to incorporate scientific research evidence with clinical expertise to aid in assessing and addressing neonatal EOL symptoms.…”
Section: Introductionmentioning
confidence: 99%